2017
DOI: 10.3906/biy-1702-19
|View full text |Cite
|
Sign up to set email alerts
|

Application of proline to root medium is more effective for amelioration of photosynthetic damages as compared to foliar spraying or seed soaking in maize seedlings under short-term drought

Abstract: Exogenous proline (PRO) at low concentrations can enhance drought stress tolerance in different application modes such as application to rooting medium, foliar spray, and seed soaking. However, there is no information about which application mode is more effective for increasing the drought tolerance. Comparative effects of 1, 10, and 20 mM PRO applications through three application modes to hydroponically grown seedlings were examined under short-term drought stress in maize seedlings. Effects on leaf water p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
1
0
3
Order By: Relevance
“…It may probably result from photoinhibition [ 32 ] occurring either due to decrease in its rate constant of photochemistry (leading to rise in Fo) or by increase in rate constant of non-radiative dissipation of excitation energy (leading to decrease in both Fo and Fm) [ 33 ]. These results and arguments are similar to those of [ 34 ] who also reported that application of higher proline dose caused a decline in Fv/Fm in maize plants.…”
Section: Discussionsupporting
confidence: 91%
“…It may probably result from photoinhibition [ 32 ] occurring either due to decrease in its rate constant of photochemistry (leading to rise in Fo) or by increase in rate constant of non-radiative dissipation of excitation energy (leading to decrease in both Fo and Fm) [ 33 ]. These results and arguments are similar to those of [ 34 ] who also reported that application of higher proline dose caused a decline in Fv/Fm in maize plants.…”
Section: Discussionsupporting
confidence: 91%
“…Bitkiler, stres koşulları altında ozmolit birikimi ile tolerans kazanır. Prolin su eksikliği sırasında ozmotik düzenleyici olarak bitkilerde rol oynayan uyumlu çözünenlerden biridir ve ayrıca diğer çevresel stres faktörlerine karşı savunma sistemlerinde yer alır [17]. Her iki domates çeşidinin prolin seviyesi tüm PEG uygulamalarıyla birlikte kontrol grubuna kıyasla arttığı belirlenmiştir.…”
Section: Kuraklık Stresinin Prolin Seviyesi üZerine Etkisiunclassified
“…Birçok bitkide, biyotik ve abiyotik strese yanıt olarak serbest prolin birikir. Prolin kuraklık stresinin neden olduğu su eksikliğine karşı bitki stres toleransını artırmada etkili bir bileşiktir [16,17].…”
Section: Introductionunclassified
“…Proline is a signaling molecule and it regulates plant growth by triggering the signaling processes (Yildiz and Terzi, 2013). Moreover, Pro, also improves synthesis of photosynthetic pigments, normal photochemical functioning, activities of antioxidants and regulates Na + compartmentalization which protects the plants from adverse effects of SS thus resulting in a substantial improvement in growth and development (Alam et al, 2016;Demiralay et al, 2017;Rady et al, 2019).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%